2006
DOI: 10.1111/j.1468-0491.2006.00324.x
|View full text |Cite
|
Sign up to set email alerts
|

Europeans outside the EU: Telecommunications and Electricity Reform in Norway and Switzerland

Abstract: Norway and Switzerland are two western Europe states that are not members of the European Union (EU), and they are among a number of small and economically open states in which reform of economic sectors is seen to be incremental and reactive. This article poses two questions about the reform of telecommunications and electricity in the two countries. First, what impact has nonmembership of the EU had on the reforms? Second, have their small and open economies and policymaking systemsconceptualized as "social … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 39 publications
0
16
0
Order By: Relevance
“…Large and small companies disagreed on the extent of liberalization and the unions neatly opposed it. This ambiguous stance was backed by the Swiss electricity supply association, which asked for a slow process and for compensation to losers (Bartle , pp. 421–424).…”
Section: Discussion Of Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Large and small companies disagreed on the extent of liberalization and the unions neatly opposed it. This ambiguous stance was backed by the Swiss electricity supply association, which asked for a slow process and for compensation to losers (Bartle , pp. 421–424).…”
Section: Discussion Of Resultsmentioning
confidence: 99%
“…As for coordination in the labor market, only the UK, a prototypical LME, scores low in the distribution (below 0.333). At intermediate levels of coordination (0.334 to 0.666) lie Switzerland, whose system of industrial relations is considered a very light/liberal variant of corporatism (Afonso & Mach , p. 113; Bartle ); Denmark, which has decentralized its industrial relations; and two Southern countries (Portugal and Spain) that are typically included into a hybrid category, characterized by weak coordination. France, by a small margin, falls within the intermediate category, as its industrial relations “came to resemble those of market capitalist Britain” (Schmidt , p. 535).…”
Section: Data and Operationalizationmentioning
confidence: 99%
“…The existing explanations for the incorporation of EU rules into domestic law‐making stem from case studies and hint at the role of the development of EU policies, particularistic domestic (economic) interests and characteristics of the domestic decision‐making process (e.g., Maggetti et al. , Jegen , Bartle , Mach et al. ).…”
Section: State Of Research: Switzerland's Policies Towards the Eumentioning
confidence: 99%
“…Although the incorporation of EU rules into domestic legislation can without doubt have economic advantages, case‐study research showed that it is not trivial to attribute a general integration interest to certain sectors. For example, Maya Jegen () analysed the particularistic interests in the energy sector and Ian Bartle () analysed the firm‐specific interest of electricity suppliers. Fortunately, political scientists invested a great effort in researching the Swiss political decision‐making process.…”
Section: State Of Research: Switzerland's Policies Towards the Eumentioning
confidence: 99%
“…As shown in the development of an EC telecoms policy, it was accepted as part of the EC agenda only after telecoms had become an issue of trade and industry. Developing discussions of EC's reform processes, Bartle (2006) summarizes three analytical frameworks of 'national patterns approach', 'policy sector approach' and 'international regime approach'. Like neorealism and neofunctionalism, this classification also focuses on national factors and policy norms and ideas emanating from international institutions, but it suggests different frameworks according to policy areas, which causes the problem of generalization.…”
Section: May 2008mentioning
confidence: 99%